An optimal sliding mode congestion controller for connection-oriented communication networks with lossy links - Bartoszewicz, Andrzej; Leśniewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
A new discrete-time sliding-mode congestion controller for connection-oriented networks is proposed. Packet losses which may occur during the transmission process are explicitly taken into account. Two control laws are presented, each obtained by minimizing a different cost functional. The first one concentrates on the output variable, whereas in the second one the whole state vector is considered.
Keywords: optimal control; sliding-mode control; flow control; discrete-time systems